Neutrophils: mediating TelOxidation and senescence - Jacome Burbano, Maria Sol (EMBO J, 2021)
Cellular senescence is considered to be a major driver of aging, yet the mechanisms explaining the accumulation of senescent cells during life time remain unclear. In this issue, Lagnado et al (2021) show that neutrophils can trigger the senescence of neighboring cells by transmitting reactive oxygen species (ROS), which they normally produce to fight pathogens. The main genomic targets of the neutrophil‐mediated ROS damage are telomeres, supporting an intimate interplay between telomere homeostasis and oxidative stress in senescence and consequently aging.